The Corruption Eradication Commission Role In Supervising Of The Social Assistance Funds Distribution From The Maslahah Mursalah Perspective - Musyafaah, Nur Lailatul; Fauziyyah, Risma; Khusnah, Rozinatul; Alim, Syaiful (STAI Bumi Silampari, 2023)
During the Covid-19 pandemic, many Indonesians are experiencing financial difficulties, so the government funds social assistance. Social assistance funds are prone to corruption, so the Corruption Eradication Commission (KPK) plays a role in supervising the distribution of funds. This article discusses the role of the KPK in supervising social assistance funds during the pandemic of Covid-19 from the perspective of maslahah mursalah. This research library research. The primary data source is the Circular Letter of the Corruption Eradication Commission (SE KPK) Number 8 of 2020, SE KPK Number 11 of 2020, and Letter KPK Number B/1939/GAH.00/01-10/04/2020. Secondary sources in this study are materials/data regarding data of KPK, maslahah mursalah, and social assistance funds. The data obtained are then analyzed through inductive analogies with the maslahah mursalah. This study concluded that the Corruption Eradication Commission (KPK) has a role in supervising social assistance funds through preventive measures, coordination, and monitoring of the distribution of social assistance funds so that some parties commit no abuse. The KPK’s role in supervising social assistance funds is relevant to maslahah mursalah, primarily to safeguard property and maintain state finances.